2012
DOI: 10.1088/2041-8205/758/2/l40
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Internal Magnetic Structure of the Solar Network

Abstract: We analyze the spectral asymmetry of Stokes V (circularly polarized) profiles of an individual network patch in the quiet Sun observed by Sunrise/IMaX. At a spatial resolution of 0.15 ′′ − 0.18 ′′ , the network elements contain substructure which is revealed by the spatial distribution of Stokes V asymmetries. The area asymmetry between the red and blue lobes of Stokes V increases from nearly zero at the core of the structure to values close to unity at its edges (one-lobed profiles). Such a distribution of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
4
29
1
Order By: Relevance
“…Many magnetic canopies were found to lie above essentially field free regions. The canopies found here agree with the model proposed by Grossmann-Doerth et al (1988) for the production of the Stokes V area asymmetry and the observational results presented by Rezaei et al (2007), Narayan &Scharmer (2010) andMartínez González et al (2012). All magnetic features were observed to expand with height and many isolated MFCs merged to form comparatively large expanses of magnetic field at log(τ) = −2.3.…”
Section: Discussionsupporting
confidence: 90%
“…Many magnetic canopies were found to lie above essentially field free regions. The canopies found here agree with the model proposed by Grossmann-Doerth et al (1988) for the production of the Stokes V area asymmetry and the observational results presented by Rezaei et al (2007), Narayan &Scharmer (2010) andMartínez González et al (2012). All magnetic features were observed to expand with height and many isolated MFCs merged to form comparatively large expanses of magnetic field at log(τ) = −2.3.…”
Section: Discussionsupporting
confidence: 90%
“…Flux tubes expand with height owing to pressure balance and magnetic flux conservation. Martínez González et al (2012) also analyzed IMaX L12 data of a single network element and found evidence for a canopy. By studying a statistical ensemble of BPs, mostly consisting of internetwork elements, we were able to show that the spatial distribution of the asymmetry is consistent with the presence of a canopy, thus further supporting the model of Grossmann-Doerth et al (1988) and Solanki (1989).…”
Section: Discussionmentioning
confidence: 99%
“…This situation has changed with the availability of data recorded by the Sunrise balloon-borne observatory, which have allowed magnetic elements even in the internetwork quiet Sun to be spatially resolved (Lagg et al 2010) and have allowed the internal structure of network magnetic features to be probed (Martínez González et al 2012) providing a good opportunity to revisit BPs and to compare their observational properties with predictions from state-of-the-art radiation magnetohydrodynamic (MHD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Sect. 4.3) values of up to 80%, because under such an assumption this factor has to reproduce both the real stray light and the magnetic filling factor inside a pixel (but see also Lagg et al 2010;Martínez González et al 2012). Our choice of the inversion setup yields an acceptable fit to the Stokes I profiles (indicating a reasonable choice of α) while the polarization signal in Stokes QUV is less well reproduced because of our one-component assumption.…”
Section: Inversion Setupmentioning
confidence: 96%